Greek War of Independence (Greek Revolution) 1821 – 1832 - صلاط أيمن (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The weakness of the Ottoman Empire and the complications within it increased the intensity of the struggle between European countries to share the empire’s lands, and what was known as the Eastern Question emerged at that time, which was worthy of the attention of historians, especially during the period of the Greek Revolution in the 1820s. The topic of the Greek Revolution covers a relatively short period of Ottoman European history, lasting about a decade from 1821-1832, known as the Greek War of Independence. There is no doubt that the two factors of Ottoman weakness and external interference were the most prominent and distinguishing factors of the Turkish-Greek conflict, in addition to the sympathy of European public opinion for the Greek revolution, which almost failed after the Egyptian intervention on the side of the Ottomans, but the Pnilike Hetaria Association had the largest role in the dream of independence and the formation of "Grand Greece". The Greeks succeeded in reaching their goal through political action, which was coupled with military action and external support. In addition to this was the Europeans’ admiration for ancient Greek civilization and the religious connection between Greece and Europe, especially Russia. The aid of European institutions was also of great importance to the Greeks, but at the time it was Russia supports the forces of the Greek Revolution, it seemed clear that it was not the final decision-maker in the future of that revolution, because Britain was managing the axis of politics in the Balkans and proved that it was the engine of global politics at that time by adopting a different duality with the Ottoman Empire. On the one hand, it was seeking to contain Russian attempts, to intervene in the Greek Revolution by preserving the integrity of the Ottoman Empire and not allowing Russia to establish a “Greek state” affiliated with it. On the other hand, it took upon itself to establish this state instead of Russia when it succeeded in concluding the London Protocol in February 1830, which stipulated the independence of Greece. With this policy, Britain strengthened the division of the Ottoman Empire due to its weakness, so that it could control the regions subject to it in future stages that became clear in the late nineteenth century and the beginning of the twentieth century.